Coexistence of hashimoto s thyroiditis with papillary thyroid carcinoma: a single center experience (Annals of Medical Research, 2021)
Aim: A positive correlation between Hashimoto's thyroiditis (HT) and papillary thyroid cancer (PTC) is determinated in studies based on histopathological examination of the thyroidectomy materials, but this correlation is not determinated in studies based on Fine Niddle Aspiration Biopsy (FNAB). In this study, the histopathologic results of bilateral total thyroidectomy (TT) specimens were studied for outcomes of PTC association with HT and its relationship with clinical and pathological prognostic factors.